PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA E-COMMERCE SHOPEE DI WILAYAH SURAKARTA - Intan Fitriandani (JURNAL WIRANOMIKA, 2024)
This study aims to determine the effect of Product Quality (X1), Perceived Price (X2), and Brand Image (X3) on Purchase Decision (Y) in e-commerce Shopee in Surakarta area. This study used multiple linear regression analysis which was analyzed using the SPSS 25 program. The results of the multiple linear regression analysis equation obtained were Y = 8.237 + 0.053 + 0.384 + 0.406 + e. The data used is primary data using the number of respondents 100 e-commerce users in the Surakarta area. The results showed that Product Quality (X1) t count (0.665) < t table = (1.984), the hypothesis is accepted, meaning that there is no significant effect between Product Quality (X1) on Purchase Decisions (Y) on e-commerce Shopee in Surakarta region. Perceived Price (X2) t count (4.570) > t table (1.984), the hypothesis is rejected, meaning that there is a significant influence between Perceived Price on Purchase Decisions at e-commerce Shopee in Surakarta area. Brand Image (X3) t count (5.476) > t table (1.984), the hypothesis is rejected, meaning that there is a significant influence between Brand Image on Purchase Decisions at e-commerce Shopee in Surakarta area. F test results obtained F count (66.655) > F table (2.70), the hypothesis is rejected, meaning there is a simultaneous influence between Product Quality (X1), Perceived Price (X2), and Brand Image (X3) on Decision Purchase (Y) on e-commerce Shopee in Surakarta area. Of the three variables that most dominantly influence purchasing decisions (Y) is brand image (X3) where the value of t count (5.476) > t table (1.984), means that the hypothesis is not proven true. From the test results of the Coefficient of Determination (R2) obtained a result of 0.665 (66.5%), proving that simultaneously there is an influence between the independent variables, namely Product Quality (X1), Perceived Price (X2), and Brand Image ( X3) to the dependent variable, namely Purchase Decision (Y) on e-commerce Shopee in Surakarta area. While the remaining 33.5% is influenced by other factors not included in this research.Keywords : Product Quality, Perceived Price, Brand Image, Purchase Decision